Welcome in! How the academy can warrant recognition of young children as researchers. Issue 2 (4th March 2017) - Murray, Jane
Abstract : The academy has tended to marginalise young children as researchers (YCAR), even in matters affecting them, which denies young children agency and amounts to social injustice. Drawing on the YCAR study, which adopted a qualitative 'jigsaw' methodology to co-research with children aged four to eight years ( n = 138), their parents, practitioners, and professional researchers, this article considers epistemological factors and epistemological categories that may support young children's research behaviours in everyday activities. Those support structures are helpful in securing a warrant for recognising young children's self-directed research on the academy's terms. That recognition has potential to reposition young children away from the margins of research to an intrinsic position in research concerning matters that affect them, securing their rights as researchers. Such research can inform early childhood policy and practice in a deeply grounded manner that values young children as competent thinkers with expertise concerning their own lives.